The doctrine of civil law and the ruling concepts on the notion of medical malpractice - Białkowski, Michał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The objective of this paper is to present medical malpractice in cases related to civil liability. The article outlines the evolution of the perception of a physician’s civil liability, and against this background presents the concept and various divisions of medical malpractice represented in polish jurisprudence. The doctrine of civil law is nowadays consensus on the fact that the concept of medical malpractice includes behaviour associated with an offense against the principles of medical knowledge. But it is not commonplace knowledge even among lawyers and medical malpractice often becomes a collective term to describe the fault of members of medical staff or negligence. Not only is this issue important to law and medical communities but also to public opinion that expresses a growing interest in this subject. It may not come as a surprise, after all, that physicians are treated as professionals of public trust, thus entrusted with a patient’s fate as well as with trust of the family,they are obligated to perform their duties with accordance to current medical knowledge.